Amino acids integrate behaviors in nerveless placozoans - Nikitin, Mikhail A.; Romanova, Daria Y.; Borman, Simkha I.; Moroz, Leonid L. (Frontiers in Neuroscience, 2023)
Placozoans are the simplest known free-living animals without recognized neurons and muscles but a complex behavioral repertoire. However, mechanisms and cellular bases of behavioral coordination are unknown. Here, using Trichoplax adhaerens as a model, we described 0.02–0.002 Hz oscillations in locomotory and feeding patterns as evidence of complex multicellular integration; and showed their dependence on the endogenous secretion of signal molecules. Evolutionary conserved low-molecular-weight transmitters (glutamate, aspartate, glycine, GABA, and ATP) acted as coordinators of distinct locomotory and feeding patterns. Specifically, L-glutamate induced and partially mimicked endogenous feeding cycles, whereas glycine and GABA suppressed feeding. ATP-modified feeding is complex, first causing feeding-like cycles and then suppressing feeding. Trichoplax locomotion was modulated by glycine, GABA, and, surprisingly, by animals’ own mucus trails. Mucus triples locomotory speed compared to clean substrates. Glycine and GABA increased the frequency of turns. The effects of the amino acids are likely mediated by numerous receptors (R), including those from ionotropic GluRs, metabotropic GluRs, and GABA-BR families. Eighty-five of these receptors are encoded in the Trichoplax genome, more than in any other animal sequenced. Phylogenetic reconstructions illuminate massive lineage-specific expansions of amino acid receptors in Placozoa, Cnidaria, and Porifera and parallel evolution of nutritional sensing. Furthermore, we view the integration of feeding behaviors in nerveless animals by amino acids as ancestral exaptations that pave the way for co-options of glutamate, glycine, GABA, and ATP as classical neurotransmitters in eumetazoans.